Cotton Fields No More : Southern Agriculture, 1865-1980. - Fite, Gilbert C., 1918-2010 (New perspectives on the South., 1984)
No general history of southern farming since the end of slavery has been published until now. For the first time, Gilbert C. Fite has drawn together the many threads that make up commercial agricultural development in the eleven states of the old Confederacy, to explain why agricultural change was so slow in the South, and then to show how the agents of change worked after 1933 to destroy the old and produce a new agriculture. Fite traces the decline and departure of King Cotton as the hard taskmaster of the region, and the replacement of cotton by a somewhat more democratically rewarding group.